EFL Students’ and Teachers’ Perceptions on Written Corrective Feedback during Blended Learning - Firmansyah, Firmansyah; Muhayyang, Maemuna; Tahir, Muh. (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
This study aims to determine EFL students’ and teachers’ perceptions on written corrective feedback (WCF) during blended learning. Interviews, and focus group discussions (FGD) were the instruments used in this study. The researchers used a descriptive qualitative methodology for the research design of this study. Two English teachers and eight students in the IX grade for the academic year 2022–2023 served as the study's subjects. They were selected through a purposive sampling technique. The findings showed that the implementation of WCF was perceived positively and negatively by the EFL students at SMP Negeri 3 Galesong Selatan. The students who had favourable opinions reported that the implementation of WCF was motivating, interesting, and useful. Meanwhile, the students with negative perceptions confirmed that they were demotivated because they had to clarify the WCF provided by the teachers. Further, the EFL teachers also had favourable opinions of WCF as it applied to students in blended learning. They argued that WCF was important, motivating, and helpful for students to recognize their errors. In summary, the researchers concluded that both EFL students and teachers at SMP Negeri 3 Galesong Selatan had favourable perceptions of WCF implementation during blended learning.